Role of Artificial Intelligence in Cost Reduction and Competitiveness Achievement - Sadeq Dhahir Farhan Alzaidi; Hussein Falah Hasan (International Forum of Researchers and Lecturers, 2025)
The research addresses the role of artificial intelligence technologies in achieving cost reduction, achieving a sustainable competitive advantage, and improving the operational performance of companies, by analyzing how these technologies reduce costs. The research is based on a basic hypothesis that